Hubungan antara umur dan kelainan genetalia dengan kejadian abortus spontan - Ana Ria Wiharti; Heni Puji Wahyuningsih; Sari Hastuti (Jurnal Kesehatan Ibu dan Anak, 2016)
Abortion rate in Panembahan Senopati General Hospital BantuI had trend which always increased every year.Misscariage caused by three factors, maternal (genital abnormalities, Hines, rhesus type, contractionsstimultion, placental circulation disorder, age), fetus and paternal factors. Complication of abortion arebleeding, reproduction organ damage, infection and end in infertility and ectopyc pregnancy. Purpose to identifycorrelation of age and genital abnormalities with spontaneous abortion Panembahan Senopati GeneralHospital Bantu12011. Methods analitic observational with crossectional design. Sample in this study is pregnantwomen who match with criteria used consecutive sampling are 230 participants. Intrument of this study ismaster table and used secondary data (medical record). Hipotesis analysis used chisquare. Result: prevalenceof spontaneous abortion in pregnant women at the age of < 20 years old or > 35 years old are 57,1% and inpregnant women in 20-35 years old are 39,8%. Prevalence of spontaneous abortion in pregnant women witngenital abnormalities are 62,7% and for pregnant women with normal genital are 44,1%. Result analysisbivariabel of age with spontaneous abortion acquared p-value = 0,00 < 0,05, and analysis of genitalabnormalities with spontaneous abortion acquared p-value = 0,01 < 0,05. Whereas RP score forage is 1,4 withconfidence interval 95%. And RPscore of genital abnormalities is1,4 with confidence interval 95%.Conclusion:there are correlation of age and genital abnormalities with spontaneous abortion. Genital abnormalities willincreased spontaneous abortion possibility.